The high energy neutrino cross-section in the Standard Model and its uncertainty - Cooper-Sarkar, A; Mertsch, P; Sarkar, S (2011)
Updated predictions are presented for high energy neutrino and antineutrino charged and neutral current cross-sections within the conventional DGLAP formalism of NLO QCD using modern PDF fits. PDF uncertainties from model assumptions and parametrization bias are considered in addition to the experimental uncertainties. Particular attention is paid to assumptions and biases which could signal the need for extension of the conventional formalism to include effects such as ln(1/x) resummation or non-linear effects of high gluon density.